Evolução de capacidades no setor de vinhos finos do Vale dos Vinhedos – RS - Lopes, Patrícia Rafaeli (Universidade do Vale do Rio dos Sinos, 2019)
This study aims to analyze the fine wine sector of Vale dos Vinhedos observing its technological trajectory in order to identify through the elements listed in the literature whether this sector is undergoing a catching-up process. Giuliani, Morrison and Rabellotti (2011) explain that while many discussions about catching-up are being held in terms of countries, there is also a current in the literature that analyzes the catching-up of sectors, object of this dissertation. Rio Grande do Sul presents a successful performance in the wine area, as the state concentrates the largest number of companies in the sector in the country, established in Vale dos Vinhedos, Campos de Cima da Serra, Serra do Sudoeste and Campanha. Vale dos Vinhedos has been outstanding in relation to the production and marketing of fine wines (considered premium quality products) and sparkling wines, with international recognition, so the interest of this dissertation in this sector and region. The analysis was carried out by means of a qualitative field research, in which 10 winemakers from 10 wineries and 5 representatives from institutions were interviewed in person from April to June 2019. The data were analyzed with the aid of the Nvivo® system, with the objective of better capturing in the interviews the essential elements that characterize a catching-up or technological upgrading process, organized in the categories of technology, knowledge, market, management and institutions. The main results are: 1) the Vale dos Vinhedos wineries group underwent a technological upgrade from 2005 to 2010, when there was a need for technological adaptation due to changes in the market after the entry of wines. imported, requiring an industry upgrade to compete with these new products; 2) it can now be said that the sector is not undergoing a new technological upgrade, since, according to the perception of the wineries and institutions interviewed, the Vale dos Vinhedos sector is already technologically paired with considered frontier production processes, and processes linked to viticulture and 3) points to a possible new upgrading when the sector faces a qualification of national demand, as this is the main market focus of the studied wineries. The issue is the challenge of increasing per capita consumption of fine wines. There are efforts by firms and institutions to make this happen in the near future, such as: focus on the development of easier consumer products, development of wine tourism to promote the region's products, recognition of its products in international competitions and negotiations to reduce Tax Burden. In terms of the study's contribution, the following stand out: 1) the relevance of analyzing the competitive conditions of a productive sector that has as its technological trajectory the offer of (increasingly) premium products; and 2) the importance of analyzing the trajectory of the sector, at the mesoeconomic level, which allows us to understand the roles of different actors in the sectoral development process: firms of different sizes and behaviors, public and private institutions. In the case of the sector investigated, different actors played important roles in the segment's trajectory, indicating that collective and coordinated efforts are necessary for technological leaps to occur.
Keywords: Catching-up setorial; Upgrading; Inovação e concorrência setorial; Setor de Vinhos Finos; Vale dos Vinhedos/RS/Brasil; Sector Catching-up; Upgrading; Innovation and sectoral competition; Fine Wine Sector; Vale dos Vinhedos / RS / Brazil; ACCNPQ::Ciências Sociais Aplicadas::Economia